Ecological Survey of Snakes around Ajdabiya, Eastern Libya, and the Effects of Human Disturbance on Their Populations - Dakheel, Husam (Journal of Pure & Applied Sciences, 2025)
This research presents the first detailed examination of snake populations and the threats they face in the vicinity of Ajdabiya, Eastern Libya. A total of five snake species from four families (Elapidae, Viperidae, Colubridae, and Psammophis sibilans) were recorded. The conflict between humans and wildlife has long been a pressing issue, exacerbated by urban expansion and the growth of residential areas. Rapid development has made urban sprawl inevitable, leading to increased demand for land not only for agriculture but also for livestock grazing in recent years. As a result, vast areas have suffered severe degradation, contributing to the decline of various ecological communities, including snakes. We strongly recommend immediate action, including support for the Ajdabiya National Reserves Establishment Programme, reinforcement of the Red Line Environmental Conservation Initiative, and the expansion of broader environmental protection programmes to mitigate further ecological harm.